The House of the Scorpion - Farmer, Nancy, 1941- (New York Simon Pluse, 2004)
In a future where humans despise clones, Matt enjoys special status as the young clone of El Patrón, the 142-year-old leader of a corrupt drug empire nestled between Mexico and the United States
Keywords: Human cloning -- Juvenile fiction -- Human cloning